Briket Batok Kelapa, Energi Alternatif Ramah Lingkungan bagi Desa Kote, Kabupaten Lingga, Kepulauan Riau - Nur, Syarifudin; Nurdjaman, Susanna; Abdullah, Faizal; Cahya, Brian; Al-Ghifari, Khalid (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Kote Village, located on Singkep Island in Riau Islands Province, has the potential to utilize coconut shell briquettes as a sustainable alternative energy source. Singkep Island is known for its extensive coconut trees and is a key component of the local economy. A considerable amount of coconut shell waste remains unutilized. Much of this waste is either discarded or burned without use. This underutilized potential offers an opportunity for briquette production, providing a sustainable energy solution for the village community. This community service initiative aims to reduce a region's dependence on conventional energy sources by converting coconut shell waste into briquettes. The implementation method included prototyping a pyrolysis device in Bandung, reconstructing the equipment in Kote Village, and conducting a workshop for the local community. The results show that the briquettes produced are of good quality and have a high calorific value, and the resulting liquid smoke can be used as a natural fish preservative. This initiative analyzes the environmental and economic benefits of coconut shell briquettes, demonstrating that they offer an efficient alternative energy source that can reduce environmental impact and enhance local energy resilience. Furthermore, it emphasizes the potential for local production, empowering villagers to achieve energy independence while supporting the regional economy. This method helps minimize waste while offering a replicable solution for other villages.